2017
DOI: 10.1007/s11356-017-0947-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-level engineered nanoparticles on the quorum sensing of Pseudomonas aeruginosa PAO1

Abstract: The toxicity of engineered nanoparticles (ENPs) on bacteria has aroused much interest. However, few studies have focused on the effects of low-level ENPs on bacterial group behaviors that are regulated by quorum sensing (QS). Herein, we investigated the effects of nine ENPs (Ag, Fe, ZnO, TiO, SiO, FeO, single-wall carbon nanotubes (SWCNTs), graphene oxide (GO), and C) on QS in Pseudomonas aeruginosa PAOl. An ENP concentration of 100 μg L did not impair bacterial growth. However, concentrations of 100 μg L of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…There was no difference in the growth pattern of P. aeruginosa PAO1 treated with Pb-AgNPs compared to the control cells not treated with Pb-AgNPs (Supplemental Figure 2, Supplemental material available online). Pb-AgNPs at the above mentioned concentrations had no effect on the growth of the test strain, suggesting its possible application as a true anti-QS agent (Li et al 2018).…”
Section: Growth Assaymentioning
confidence: 97%
“…There was no difference in the growth pattern of P. aeruginosa PAO1 treated with Pb-AgNPs compared to the control cells not treated with Pb-AgNPs (Supplemental Figure 2, Supplemental material available online). Pb-AgNPs at the above mentioned concentrations had no effect on the growth of the test strain, suggesting its possible application as a true anti-QS agent (Li et al 2018).…”
Section: Growth Assaymentioning
confidence: 97%
“…Additionally, 100 μg/L GO significantly promoted biofilm and protease production by P. aeruginosa PAO1 after 24 h of incubation . Compensatory release of proteases and biofilm generation were suggested as adaptive responses of P.…”
Section: Resultsmentioning
confidence: 89%
“…Here, we propose that the adsorption of signal molecules onto mineral surfaces is a universal mechanism for their reduction in the environment. The difference in physicochemical properties including the surface area, charge and adsorption capacity is the main reason behind the differences in QS quenching among the three clay minerals (Masiello et al, 2013;Duran et al, 2016;Li et al, 2018). Several mechanisms including reactive oxygen species, surface adhesion and toxic ions have been proposed for the explanation of mineral toxicity (Londono et al, 2017;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, it is speculated that the cellular density and QS-related enzyme activity may be hindered in the presence of these mineral particles. On the other hand, the minerals can reduce the extracellular concentration of signal molecules by surface adsorption (Masiello et al, 2013;Li et al, 2018). It was reported that the adsorption capacities of signal molecules, acyl-homoserine lactones (AHLs), onto minerals were in the order: montmorillonite > kaolinite > goethite (Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%